Evaluation of Temperature and Storage Conditions of Onggok flour (Manihot esculenta) Viewed from Physicochemical Parameters - Nadia Massita; Arita Dewi Nugrahini (Journal of Food and Agricultural Product, 2026)
Onggok flour is a flour obtained by grinding dried and sieved cassava tubers until it becomes coarse granules in certain sizes. Storage will greatly affect the characteristics of the material as well as its shelf-life. This study aimed to determine the value of physicochemical parameters of onggok flour at storage temperatures of 300C and 500C. In addition, this research also aimed to evaluate the physical condition of the existing warehouse in the company. The study was conducted by storing onggok flour at two different temperatures for five weeks. In assessing the best storage temperature, the main characteristics will be assessed as a reflection of the quality of onggok flour quality, defined into 6 parameters based on Indonesian National Standard and the industry’s internal standard, such as moisture content, pH, colour, degree of acidity, and viscosity at 500C and 900C. The physicochemical parameter values of onggok flour obtained at 310C and 550C were 9.37% and 8.88% for moisture content, 3 ml and 3.07 ml NaOH for acidity degree, 82.26 and 82.46 for colour (lightness), 0.31 and 0.33 for viscosity at 500C, 0.26 and 0.28 for viscosity at 900C, and 5.22 and 5.27 for pH, respectively. 5 of the 6 parameters showed a better characteristic at 550C, so the more appropriate temperature for onggok flour storage is 550C. The suggested improvements includes adding more vents, roof plasterboard, wooden pallets, and temperature control devices, reduction of sack piles, periodic floor cleaning and the increase in the number and type of pest control instruments. Keywords: onggok flour, temperature, storage, warehouse